Produção de anticorpos monoclonal murino dirigido contra a PBP2a do S. aureus resistente a meticilina - Querino, Gislaine Aparecida [UNESP] (2013)
S. aureus is, without doubt, the most important human pathogen among staphylococci. The emergence and dissemination of progressive resistance to methicillin had great impact on therapy of staphylococcal infections. The mechanism of resistance to methicillin developed by S. aureus is related to the alteration of penicillin binding proteins, the PBPs. Staphylococcus. aureus produces five types of PBPs: 1,2,3,3 ', and 4. Strains of S. aureus resistant to methicillin produce a new PBP, PBP2a the acquired from other strains of staphylococci. Several methods are used for detection of methicillin resistance in S. aureus. Among them, the detection of PBP2a by latex agglutination methods using monoclonal antibody specific for the antigen directed PBP2a. In the present study, murine monoclonal antibodies directed against the PP2A methicillin resistant S. aureus were produced by cell fusion using spleen cells from immunized BALB / c mice. Five MRSA fusions were performed and the culture supernatants were screened by testing indirect ELISA. Were built and tested in 1236 hybrids and nine of them were reactive after the 4th indirect ELISA test. The nine hybrids were tested against different bacteria to observe inhibition of growth. This work focused on the production of murine monoclonal antibody for use in rapid detection tests